ЗАКЛЮЧЕНИЕ ИНДИВИДУАЛЬНЫХ ТРУДОВЫХ ДОГОВОРОВ С ПРОФЕССИОНАЛЬНЫМИ СПОРТСМЕНАМИ И ТРЕНЕРАМИ - Босый, Дмитрий (SUPREMANCE OF LAW, 2018)
In the article the features of entering into individual labour contracts are illuminated with professional sportsmen and trainers. Relevance of the topic arises from contradictory legislation, governing the work of professional athletes and coaches that hampersuniform application of the legal norms.
Keywords: individual employment contract; professional athlete; coach; labor legislation